(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
هدفت الدراسة الحالية إلى تعرّف الفروق في بعض السمات المتقابلة للشخصية عند الشباب الجامعي وفقاً لمتغيري الجنس والتخصص الأكاديمي، وقد بلغت عينة الدراسة /354/ طالباً وطالبة من ذوي التخصصات النظرية والتطبيقية في جامعة تشرين ــــــــ فرع طرطوس، وكانت أداة الدراسة المستخدمة قائمة "ميلون" للشخصية والتي تتضمن /180/ بنداً موزعة على ثلاثة مجالات من السمات المتقابلة للشخصية، واقتصرت الدراسة الحالية على الجانب الدافعي( تعزيز اللذة ـــــــــــــتجنب الألم، الانغماس الذاتي ــــــــــالاهتمام بالآخرين، التكيف النشط ـــــــــــــالتكيف السلبي). وكانت أهم نتائجها ما يأتي: - إنّ السلم الترتيبي لانتشار سمات الشخصية في الجانب الدافعي للشخصية من الأعلى إلى الأدنى هو: تجنب الألم، الانغماس الذاتي، تعزيز اللذة، الاهتمام بالآخرين، التكيف النشط، التكيف السلبي. - عدم وجود فروق في بعض السمات المتقابلة بين الذكور والإناث الجامعيين، إلّا في سمة واحدة هي سمة الانغماس الذاتي ــــالاهتمام بالآخرين لصالح الإناث. - عدم وجود فروق في بعض السمات المتقابلة بين الطلبة الجامعيين في الكليات التطبيقية والنظرية، إلّا في سمة واحدة هي سمة التكيف النشط ـــــــــــالتكيف السلبي لصالح الكليات النظرية. The aim of this current study is to recognize the differences of some opposite Personality traits of students university according to the variables of sex and academic specialty. T specialty at Tishreen university- Tartous branch. The tool of the search is Millon Index of Personality Styles Revised, which contain /180/ items divided into three scales of opposite traits of personality. This study concentrates on the motivated side: Pleasure- Enhancing, Pain- Avoiding, Self-Indulging, Other- Nurturi, Actively Modifying, Passively Accommodating. The most important results are as following: - The gradual sequence of the opposite Personality traits according to the motivated side is arranged from the highest to the lower: Pain- Avoiding, Self-Indulging, Other- Nurturi, Actively Modifying, Passively Accommodating. -The only difference in some opposite traits between male and female university students is Self-Indulging- Other- Nurturi, on the part of female students. -The only difference among university students at applied and theoretical traits is Actively Modifying- Passively Accommodating, on the part of theoretical faculties.